UJI VALIDITAS MEDIA SMOSIS (SMART MONOPOLY SYMBYOSIS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS III - Linda Melina Putri; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the validity of SMOSIS (Smart Monopoly Symbiosis), an active and effective learning medium developed to improve students' critical thinking skills. The SMOSIS (Smart Monopoly Symbiosis) medium is inspired by the Monopoly game and has been developed into a creative and innovative learning medium, making it engaging and challenging for students while helping them create a learning environment that is not boring and fostering their critical thinking skills. Validation was conducted by two experts, namely a subject matter expert and a media expert, using a Likert scale-based assessment instrument. This research is a development study with a descriptive quantitative approach. Data collection techniques include interview sheets, observations, questionnaire sheets, test sheets, and validation sheets. The validation results by the subject matter expert showed a score of 90% (very valid category), and the media expert obtained a score of 83.75% (very valid category). The overall average validation score for the SMOSIS (Smart Monopoly Symbiosis) media is 86.87%, indicating that this media falls into the ‘highly valid’ category and is suitable for use in the learning process. Thus, the SMOSIS (Smart Monopoly Symbiosis) media has been proven to meet the criteria for content, presentation, and technical aspects and has great potential to support the development of critical thinking skills among students. This finding is expected to serve as a foundation for further development and implementation of creative and innovative media in primary school education.